Boosting Gen Z’s Adversity Quotient through Creative Group Counseling with Islamic Values - Hartika Utami Fitri; Nurul Astuty Yensy; Sudarwan Danim (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Generation Z is a group that lives in a fast-paced and dynamic technological environment, so it is vulnerable to various psychological pressures, including quarter life crises. This condition is characterized by identity confusion, anxiety about the future, and uncertainty about the direction of life which has an impact on low ability to face difficulties (Adversity Quotient/AQ). This study aims to test the effectiveness of creative group counseling that is integrated with Islamic values in increasing AQ in Gen Z who are experiencing a quarter life crisis. The research method used is pre-experimental with a One Group Pretest–Posttest design. The research subjects amounted to seven Gen Z people who were selected using purposive sampling. The research instruments are in the form of AQ and quarter life crisis questionnaires that have been tested for validity and reliability. The intervention was carried out through five sessions of counseling for creative groups based on Islamic values such as patience, tawakal, gratitude, and effort. The results of the analysis using the Wilcoxon Signed Rank Test with a Zscore = -2,410 showed a significant difference between the pretest and posttest scores (Asymp. Sig. = 0.016 < 0.05), which showed that group counseling services were effective in improving the participants' AQ. These findings confirm that the integration of psychological and spiritual approaches through creative group counseling can increase adversity questions in students .